2015
DOI: 10.1007/s11199-015-0482-0
|View full text |Cite
|
Sign up to set email alerts
|

The Exonerating Effect of Sexual Objectification: Sexual Objectification Decreases Rapist Blame in a Stranger Rape Context

Abstract: A blossoming body of research documents the effect of sexual objectification on social perception, but little is known about the consequences of sexual objectification. This paper examines how sexual objectification influences men and women's rape perceptions in case of a stranger rape. We hypothesized that victims' sexual objectification might diminish rapist blame and increase victim blame in cases of stranger rape. Fifty-eight male and 57 female Belgian undergraduate students were assigned to either a sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 41 publications
(56 reference statements)
0
55
2
1
Order By: Relevance
“…Researchers from Belgium and the UK (Bernard et al 2015) also used objectification theory in their research about the consequences of sexual objectification in cases of sexual assault. Belgian undergraduate participants read a newspaper article about a sexual assault accompanied by a picture of the woman, a model, who was assaulted.…”
Section: Dress and Sexual Assaultmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers from Belgium and the UK (Bernard et al 2015) also used objectification theory in their research about the consequences of sexual objectification in cases of sexual assault. Belgian undergraduate participants read a newspaper article about a sexual assault accompanied by a picture of the woman, a model, who was assaulted.…”
Section: Dress and Sexual Assaultmentioning
confidence: 99%
“…Similarly, Bernard et al (2015) used just world theory to investigate the extent to which the objectification of a rape survivor might alter perceptions of the perpetrator. The dependent variables were the extent to which the survivor was blamed and the extent to which the perpetrator was blamed.…”
Section: Dress That Aids Sexual Objectification Of Others (Other-objementioning
confidence: 99%
See 2 more Smart Citations
“…However, media researchers have demonstrated SO of men in Western media (Elliott & Elliott, 2005;Leit, Gray, & Pope, 2002). In studies of other-objectification, results have shown that men objectify others, both men and women, whereas women objectify other women but not men (Bernard, Loughnan, Marchal, Godart, and Klein, 2015;Loughnan et al, 2013;Nezlek et al, 2015). Given this focus on men and objectification, the following research question was developed.…”
Section: Research Questionsmentioning
confidence: 99%